2016
DOI: 10.3892/mmr.2016.5010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 modulates radiation resistance through upregulation of hypoxia-inducible factor-1α-promoted glycolysis in non-small cell lung cancer cells

Abstract: Aberrant microRNA (miRNA) expression in cancer affects the transcription of target genes, and profoundly influences cancer‑associated signaling pathways. Radiation resistance is a major problem encountered in the treatment of cancer. The present study aimed to investigate the role of miRNA (miR)‑21 in the development of radiation resistance in non‑small cell lung cancer cells. A radiation‑resistant cell line was generated from A549 cells. Significant upregulation of miR‑21 was detected in the radioresistant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 26 publications
2
31
2
1
Order By: Relevance
“…Data from these studies would therefore suggest that Per2-HIF1A complex is responsible for the transcriptional regulation of miR-21 during myocardial ischemia. In line with these findings, recent studies on miR-21 in small lung cancer cells revealed a similar connection between miR-21, glycolysis and HIF1A [51]. However how miR-21 controls glycolysis would need further mechanistic studies.…”
Section: Discussionsupporting
confidence: 62%
“…Data from these studies would therefore suggest that Per2-HIF1A complex is responsible for the transcriptional regulation of miR-21 during myocardial ischemia. In line with these findings, recent studies on miR-21 in small lung cancer cells revealed a similar connection between miR-21, glycolysis and HIF1A [51]. However how miR-21 controls glycolysis would need further mechanistic studies.…”
Section: Discussionsupporting
confidence: 62%
“…The difference in fold change may be due to the difference in concentration and potency of miR-21 mimics and miR-21 inhibitors. Previous studies have also reported that HIF-1α is regulated by other miRs (14,15,30). However, the detailed mechanism by which miR-21 regulates HIF-1α is still unknown, and the regulation may involve several signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that miR-21 may regulate HIF-1α during cell adaptation to a hypoxic environment. In prostate cancer cells and in radioresistant non-small cell lung cancer cells, miR-21 increases the expression of HIF-1α and is involved in tumor bio-activities (14,15). Our previous study demonstrated that miR-21 is specifically expressed in PDL on the tension side and pressure side during orthodontic tooth movement in rats (16); however, it is still unclear whether miR-21 affects HIF-1α and osteogenic differentiation in PDLCs under hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…The consequential chronic inflammatory state caused by obesity facilitates immune dysregulation and angiogenesis [12]. Additionally, excess body fat creates an environment conducive to the enhanced glycolytic metabolism in cancer cells [13]. …”
Section: Introductionmentioning
confidence: 99%